On some controversially-discussed Raman and IR bands of beryl - Le, Thi Thu Huong (VNU, 2014)
Natural and synthetic beryl, Al2 Be3Si 6O18, from various deposits and manufacturers were investigated with Raman, I R spectroscopy, Laser Ablat ion I nductivel y Coupled Pl asma Mass Spectrometr y (LA-I CP-MS) and Electron Microprobe Analysis (EMPA). The Raman-band at 1067-1072 cm -1 and the IR-band at 1071-1207 cm -1 have been assi gned till now either to Si-O or to Be-O by di fferent studies. Following the findings in this study that the position and Full Width at HalfMaximum (FWHM) of these bands were related to the concentration of silicon but not that of beryllium, it stated that these bands were generated by the vibration ofSi-O.